Nanopathways modulating postoperative cognitive dysfunction: extracellular vesicles - Zhang, Yunmeng; Yin, Zengsheng; Zou, Zhiyong; Feng, Shangzhi; Xu, Huayang (Frontiers in Cell and Developmental Biology, 2025)
Postoperative cognitive dysfunction is a common central nervous system complication after general anesthesia in the elderly, and when it occurs, it will seriously affect the patient’s postoperative recovery and quality of life, which puts elderly postoperative general anesthesia patients at an extremely uncertain risk of postoperative psychiatric disorders or even death. It is currently believed that neuronal damage and inflammatory response due to cerebral ischemia/reperfusion injury induced by transient or repeated global cerebral ischemia during surgery are the key mechanisms for the development of postoperative cognitive dysfunction. Therefore, repairing postoperative neuronal damage and reducing neuroinflammatory responses may be an effective means of early intervention for postoperative cognitive dysfunction. Extracellular vesicles, a therapeutic tool with clear advantages in regenerative medicine, have been suggested as potential nanopathways to modulate postoperative cognitive dysfunction due to their pro-regenerative, pro-repair, and influence on immune responses. In this paper, we will summarize studies related to extracellular vesicles in the treatment of postoperative cognitive dysfunction and discuss the potential function of extracellular vesicles in nerve repair and inhibition of acute neurological inflammation, which will expand the therapeutic strategies for postoperative cognitive dysfunction and may represent the development of novel cell-free therapeutic pathways for modulating postoperative cognitive dysfunction.